Inter-Limb Coordination Variability in Ice Climbers of Different Skill Level (Baltic Journal of Sport and Health Sciences, 2011)
Research background and hypothesis. Ice climbers determine their own ascent paths by creating holes with their crampons and ice tools. The coupling of upper and lower limbs thus emerges from the icefall environment without prescriptions for one mode of coordination. Research aim. The aim of this study was to analyse the upper / lower limb coordination of ice climbers of different skill level and to explore how the environmental constraint (ice fall shape) is used by the climbers to adapt their motor behaviour.Research methods. Six elite ice climbers and ﬁ ve beginners climbed a 30m icefall, respectively in grade 5 / 5+ and grade 4. Frontal camera videotaped the ﬁ rst 15m of the ascent, then the left and right ice tools and the left and right crampons were digitalised in order to analyse the upper limbs coupling, the lower limbs coupling and the upper / lower limb coordination. Research results. The results indicated that in-phase mode of upper / lower limb coordination was the main attractor for both groups. However, elite climbers showed greater variability in their behaviour, exploring larger range of upper and lower angles (particularly vertical and crossed positions) and types of movement (ice tool swinging and ice hole hooking). Discussion and conclusions. It was concluded that holes in ice fall, and more globally ice fall shape, were affordances that induced variable upper / lower limb coordination in elite climbers, whereas beginners used a basic and stable motor organization in order to maintain body equilibrium.Keywords: upper / lower limb coordination, environmental constrains, types of movement.